The Influence of Road Infrastructure Development on Improving the Welfare of the People of Wajo Regency - Alam, Wirna Milda; S, Satriani.; Malinda, Fitalia; Syam, Muh. Syahrul; Sadriani, A. (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study analyzed the impact of road infrastructure development, especially the Lowa-Macero Road section, on improving the welfare of the people of Wajo Regency, South Sulawesi. This district has a variety of geographical characteristics, with great potential in the agricultural, fisheries and tourism sectors. Road infrastructure development is a priority for the district government to increase regional accessibility and connectivity. Data shows that the construction of the road has been carried out in stages since 2017 with a total budget of Rp41.86 billion. Analysis shows that road construction has had a significant positive impact on the welfare of the community, especially through increasing the efficiency of the distribution of agricultural products, savings in transportation costs, and opening new employment opportunities. This research confirms the importance of road infrastructure development as an effort to improve the social and economic welfare of the community in rural areas.